2013
DOI: 10.1017/neu.2013.59
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and S100B in psychotic disorders: evidence for an association with treatment responsiveness

Abstract: Serum levels of BDNF and S100B are lowered in patients with psychotic disorders across diagnostic boundaries. The differences between high and low S100B subgroups suggest a relationship between S100B, symptom dimensions and treatment response, irrespective of diagnostic categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Several studies report elevated S100B in BD ( Bartoli et al, 2020 ; da Rosa et al, 2016 ) and SCZ ( Aleksovska et al, 2014 ; Hong et al, 2016 ; Rothermundt et al, 2009 ). However, there is a positive association with symptom severity ( Futtrup et al, 2020 ; Pollak et al, 2018 ; van de Kerkhof et al, 2014 ) and reduced levels in BD after treatment of manic phase, suggesting a transient disruption of BBB that may be clinically dependent ( Tsai and Huang, 2017 ). Importantly, the current patients had relatively low symptom load, enabling putative assessment of the basal underlying BBB integrity of BD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report elevated S100B in BD ( Bartoli et al, 2020 ; da Rosa et al, 2016 ) and SCZ ( Aleksovska et al, 2014 ; Hong et al, 2016 ; Rothermundt et al, 2009 ). However, there is a positive association with symptom severity ( Futtrup et al, 2020 ; Pollak et al, 2018 ; van de Kerkhof et al, 2014 ) and reduced levels in BD after treatment of manic phase, suggesting a transient disruption of BBB that may be clinically dependent ( Tsai and Huang, 2017 ). Importantly, the current patients had relatively low symptom load, enabling putative assessment of the basal underlying BBB integrity of BD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies on the role of BDNF in the aetiology, pathophysiology and treatment of mental disorders has attracted significant interest of researchers (8). Reduced levels of BDNF have been detected in those affected by schizophrenia, depression, bipolar affective disorder, eating disorders, post-traumatic stress disorder, Huntington's disease, Alzheimer's disease, autism and in those addicted to psychoactive substances (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Karege et al (20) found reduced BDNF levels in those suffering from depression, which was later confirmed by Shimizu et al (21), Gervasoni et al (22), Piccinni et al (23), Aydemir et al (24), Yoshimura et al (25), Monteleone et al (26) and many others researching the association of these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Results are not unequivocal because no differences between SCH and HC were reported [ 34 , 37 , 38 ]; also, lower S100B was detected in SCH compared to HC [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Changes in S100B levels during antipsychotic treatment were widely studied, with contrary results. No differences [ 13 , 23 , 39 , 41 , 42 , 43 , 44 , 45 , 46 ] or decreases [ 12 , 19 , 45 , 47 , 48 , 49 ] in S100B concentrations were reported during antipsychotic treatment. Elevation in S100B levels in the patient group with predominant negative symptoms were also found [ 39 ].…”
Section: Resultsmentioning
confidence: 99%